A phylogenetic overview of Squamanita, with descriptions of nine new species and four new combinations. (4th July 2022) - Saar, Irja; Thorn, R. Greg; Nagasawa, Eiji; Henkel, Terry W.; Cooper, Jerry A.
ABSTRACT: Nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2 (ITS barcode) sequence data from eight type specimens of previously described Squamanita species were obtained. Phylogenetic analysis of ITS and partial nuc 28S rDNA data revealed Squamanita as paraphyletic splitting into two monophyletic groups, which we recognize as the genera Squamanita and Dissoderma . We accept 14 Squamanita and nine Dissoderma species, provide the first sequences of 13 of these, and describe six new species of Squamanita and three new species of Dissoderma . We transfer three species of Squamanita into Dissoderma, one into Cystoderma, and treat S. basii and S. umbilicata as synonyms of D. paradoxum. Squamanita can be distinguished from Dissoderma by the generally larger fleshier basidiomata with a tricholomatoid or amanitoid stature and yellowish to tawny brown pileus and often similarly colored stipe. Most species have cheilo- and pleurocystidia. Species of Dissoderma are small, collybioid or mycenoid, lack cystidia, and the pileus and often upper stipe are purplish gray. Both genera parasitize basidiomata of other agarics.